PEMASARAN BAWANG MERAH RAMAH LINGKUNGAN DI KABUPATEN BANTUL - Diah Rina Kamardiani; Rafli Lindusena Pratama (Universitas Galuh, 2022)
Environmentally friendly shallots in Bantul Regency have better quality than conventional systems. This study aims to (1) determine the marketing channels for environmentally friendly shallots in Bantul Regency and (2) analyze marketing costs, marketing margins, marketing benefits, and farmers' share of environmentally friendly shallots in Bantul Regency. The research method used is the descriptive analysis method. A sampling of farmers using proportional random sampling of as many as 62 environmentally friendly shallots. A sample of traders using snowball sampling of as many as 32 marketing institutions. The results showed six marketing channels in the local DIY market and four outside DIY. The highest marketing costs and margins for shallots are in marketing channel 8, with the final sales location in outside from DIY. The price of shallots and the highest marketing profit is found in marketing channel 6. The highest farmer's share value is found in marketing channel 2 with a value of 71.68% for local DIY and marketing channel 6 with 71.55% for marketing outside DIY.